Comparison of Ultrasound Treatment with Mechanical Shearing for Montmorillonite Exfoliation in Aqueous Solutions - Li, Hongliang; Zhao, Yunliang; Song, Shaoxian; Nahmad, Yuri (Journal of Minerals and Materials Research, 2015)
The exfoliated nanosheet of montmorillonite (MMT) mineral is a superior material applied in many fields especially in strengthening biodegradable polymers. The exfoliation with ultrasound treatment has been studied in this work compared with mechanical shearing through the measurements of laser size analysis, centrifugal classification and AFM. The results have shown that ultrasound treatment allowed a lower energy consumption and higher production in MMT exfoliation than the shearing method. The exfoliated nanosheets were about 1 nm in thickness, indicating that single layer of MMT has been produced.